Token transfers among great apes (Gorilla gorilla, Pongo pygmaeus, Pan paniscus, and Pan troglodytes): species differences, gestural requests, and reciprocal exchange - Pelé, Marie; Dufour, Valérie; Thierry, Bernard; Call, Josep (Journal of comparative psychology (Washington, D.C. : 1983), 2009)
Great apes appear to be the nonhuman primates most capable of recognizing trading opportunities and engaging in transfers of commodities with conspecifics. Spontaneous exchange of goods between them has not yet been reported. We tested gorillas (Gorilla gorilla), orangutans (Pongo pygmaeus), bonobos (Pan paniscus), and chimpanzees (Pan troglodytes) in a token-exchange task involving two conspecifics and a human experimenter. Tested in pairs, subjects had to exchange tokens with a partner to obtain food from the experimenter. We observed 4, 5, 264, and 328 transfers of tokens in gorillas, chimpanzees, orangutans, and bonobos, respectively. Most gifts were indirect in gorillas, chimpanzees, and bonobos, whereas most were direct in orangutans. The analysis showed no evidence of calculated reciprocity in interactions. A main finding of the study was the high rate of repeated gifts and begging gestures recorded in orangutans. This raises the question of the meaning of pointing in great apes and their ability to understand the communicative intent of others.